State tax policy in Ukraine: historical and legal aspect (based on the example of the XX century) (Law and Safety, 2020)
The scientific article is focused on the research of conceptual bases of public policy in Ukraine in the XX century in the historian legal discovery.The author has established that a financial and tax system, from the moment of declaration of the Soviet power in the territory of Ukraine, underwent serious transformation, the economic policy was directed to maintenance and strengthening of the power, preservation of an economic mechanism and creating favorable conditions for economic recovery. And the economic program is proclaimed still the Bolshevist power provided: Establishment of the progressive income tax; to cancellation of indirect taxes on necessities; establishment of high taxes on luxury goods. At the first stages of the XX century no new types of tax were established, behind an exception the expansion of the bases of application of penalties and only in 1917 it was indicated the need of legal collection of the taxes imposed by provisional government.It defined that the new economic policy was proclaimed for the purpose of restoration of commodity economy, revival of almost cancelled monetary taxes, from the ideas to a central and their principles of decentralization and partial denationalization. However, discrepancy of the made tax decisions, which took root on general level, turned out to be consequence strengthening of planned methods and mediate in administrative control, which constantly amplified arbitrariness from the state.The attention has been focused on the fact that post-war years of the government budget was subordinated to the solution of the major task to mitigation of consequences of war and restoration of the destroyed economy of the country. Growth of receipts in the budget in the form of tax from a turn and assignments from the profit of the restored industrial enterprises allowed to lower taxes on the population a few. Since January 1, 1946 a war tax was cancelled, and since September of the same year the free minimum for workers and employees was raised.The author has reasonably introduced the need for the periodization of the formation of the public tax policy, which is offered for considering through a prism of division into six main stages.
Keywords: tax system; evolution of formation of the tax system; political and legal thought; taxation